Job Fairs : Matching Firms and Workers in a Field Experiment in Ethiopia - Abebe, Girum; Caria, Stefano; Fafchamps, Marcel; Falco, Paolo; Franklin, Simon; Quinn, Simon; Shilpi, Forhad (World Bank, Washington, DC, 2017)
Do matching frictions affect youth employment in developing countries? This paper studies a randomized controlled trial of job fairs in Addis Ababa, Ethiopia. The job fairs match firms with a representative sample of young, educated job-seekers. The meetings at the fairs create very few jobs: one for approximately 10 firms that attended. The paper explores reasons for this, and finds significant evidence for mismatched expectations: about wages, about firms' requirements, and the average quality of job-seekers. There is evidence of learning and updating of beliefs in the aftermath of the fair. This changes behavior: both workers and firms invest more in formal job search after the fairs.